Human Resource Management and Labor Productivity: Does Industry Matter? - Datta, Deepak K.; Guthrie, James P.; Wright, Patrick M. (Academy of Management Journal, 2005)
There has been growing interest in the degree to which human resource systems contribute to organizational effectiveness, yet limited research attention has been paid to the contextual conditions that moderate the efficacy of these practices. In this study, we examined how industry characteristics affect the relative importance and value of high-performance work systems. Findings indicate that the impact of these human resources systems on productivity is influenced by industry capital intensity, growth, and differentiation.